Biology : (McGraw - Hill, 1995)
Reach, Teach, and Assess every student with one superb program. A captivating verbal/visual presentation weaves text and graphics together in a user-friendly, easy-to-grasp format that stimulates students' interest and performance, both in the classroom and on all types of assessment.